Batad Ifugao dictionary with ethnographic notes - Newell, Leonard E.; Poligon, Francis Bonog (Manila Linguistic Society of the Philippines, 1993)
A fuller version of Leonard Newell's Batad Ifugao Dictionary (1968). An ethnographic dictionary that is systematic, non-prescriptive and semantically sensitive. A compilation of nearly 7500 Ifugao words with full explanatory definitions of great ethnographic value and linguistic precision. Includes 16,000 brief English-Batad Ifugao index entries.
This dictionary is for the people of Ifugao, their Cordilleran neighbors and friends, as well as students of the language and culture everywhere. It includes 7,500 main entries which provide full explanatory definitions of great ethnographic value and linguistic precision.
Keywords: Ifugao language -- English. -- Dictionaries; English language -- Ifugao language. -- Dictionaries